THE MELTING POT: WHERE ARE WE! THE DEMISE OF THE EXTENDED FAMILY SYSTEM IN ZIMBABWE: A CASE OF CHIVHU RURAL COMMUNITIES IN CHIEF NESHANGWE AREA - Milton Gwakwa (European Scientific Journal, ESJ, 2014)
Prior to this present state of cultural erosion, the Shona tradition in Zimbabwe regarded the extended family system with high esteem. Those good old days seem to have disappeared and the all-embracing family concept is in a melting pot status. The paper sought to investigate the major drivers leading to “social decadence” of the extended family system and attempt to develop an indigenous socio-cultural model meant to resuscitate and revive the dying culture. A qualitative case-based research philosophy was adopted, with thirty families interviewed to provide information required to make informed conclusions on the status of extended family. Data was thematically analyzed and the results of the study indicated that the culture of extended family was in a “decomposition” state, and there was urgent need to find meaningful resuscitating strategies to keep the culture afloat. The paper recommends the adoption of the ubuntu philosophy as a basis of revival. The paper also encourages further public debate on the need to revive a culture of collectivism which once upon a time was dominant.